The Prevalence of Coronary Artery Disease in Bicuspid Aortic Valve Patients: An Overview of the Literature - Dolmaci, Onur B.; Hilhorst, Tijmen L.; Malekzadeh, Arjan; Mertens, Bart J.A.; Klautz, Robert J.M.; Poelmann, Robert E.; Grewal, Nimrat (AORTA, 2023)
The prevalence of coronary artery disease (CAD) in bicuspid aortic valve (BAV) patients is a debatable topic. Several studies have indicated that BAV patients have a lower prevalence of CAD compared with patients with a tricuspid aortic valve (TAV), but the effects of age and gender have not always been considered. This systematic review provides an overview of articles which report on CAD in BAV and TAV patients. Searches were executed in April 2021 and January 2022 according to the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-analyses) guidelines in three online databases: Medline, Embase, and Scopus. Screening and data extraction was done by two investigators separately. Primary and secondary outcomes were compared between BAV and TAV patients; a fixed effects model was used for correcting on confounders. Literature search yielded 1,529 articles with 44 being eligible for inclusion. BAV patients were younger (56.4 ± 8.3 years) than TAV patients (64 ± 10.3 years, p < 0.001). All CAD risk factors and CAD were more prevalent in TAV patients. No significant difference remained after correcting for age and gender as confounders. BAV patients have a lower prevalence of CAD and CAD risk factors compared with TAV patients. However, when the age differences between both groups are considered in the analyses, a similar prevalence of both CAD and CAD risk factors is found.
Keywords: aortic valve stenosis; atherosclerosis; bicuspid aortic valve; coronary artery disease; tricuspid aortic valve; coronary revascularization